Factors Affecting Length of Stay in the Emergency Department in Patients Who Presented with Abdominal Pain. (27th May 2020) - Dadeh, Ar-aishah; Phunyanantakorn, Pitshaya
Abstract : Objective . We aimed to identify factors affecting length of stay in the emergency department in patients who presented with abdominal pain. Methods . A retrospective cohort study was conducted from 1 January 2017 to 31 December 2017. The medical records were reviewed from 217 patients older than 15 years with the chief complaint of abdominal pain. The patients were divided into emergency department length of stay (EDLOS) < 4 hours and ≥4 hours. The two groups were compared in terms of baseline characteristics, physical examination, time of presenting, attending physicians, interdepartmental consultations, investigations, ED disposition, final diagnosis, and mortality. The significant factors affecting longer EDLOS were examined using univariate and multivariate analyses by logistic regression. Results . Factors affecting longer EDLOS were age ≥50 (odds ratio (OR) 3.17, 95% confidence interval (CI) 1.36–7.42), interdepartmental consultation ≥2 specialists (OR 71.82, 95% CI 5.67–909.51), blood testing ≥2 rounds (OR 85.6, 95% CI 4.22–1734.6), and ultrasonography (OR 8.28, 95% CI 1.84–37.26). Conclusion . The study found that the statistically significant factors that prolonged EDLOS in patients with the chief complaint of abdominal pain were age, rounds of blood test, interdepartmental consultation, and the need for ultrasonography.